Peningkatan Pengetahuan Ibu Hamil sebagai Upaya Mendukung Keberhasilan Pemberian ASI Eksklusif - Nur Anita; Nurul Aeni; Raehan Raehan; Erna Amin (Kolaborasi: Jurnal Pengabdian Masyarakat, 2026)
Introduction: Breastfeeding is a crucial component of maternal and child health, yet many mothers still face challenges related to knowledge and preparedness for exclusive breastfeeding. Community-based educational interventions are needed to improve maternal understanding and promote the use of locally available resources that may support lactation. Objective: The purpose of this service was to improve the knowledge of pregnant women regarding exclusive breastfeeding and the potential use of basil leaves as a natural support for breast milk production. Method: This public service was conducted through a community-based educational program involving lectures, interactive discussions, and practical demonstrations. Participants were pregnant women who attended the activity. Knowledge levels were measured using pre-test and post-test questionnaires, and the results were analyzed descriptively. Result: The activity involved 20 pregnant women and was implemented successfully with active participation. The results showed an increase in participants’ knowledge after the educational intervention, indicated by a higher proportion of participants in the good knowledge category and the absence of participants in the poor category at post-test. Conclusion: Educational interventions combined with participatory approaches and the utilization of local resources effectively improved pregnant women’s knowledge and readiness to support exclusive breastfeeding practices.